The Morphology of Adat: The Celebration of Islamic Holy Day in North Coast Java - Muhaimin AG. (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1999)
The main concern of this paper is to throw light on the issue as follow: what days are currently considered as Holy days, for what reason and how is the commemoration or celebration of that day performed. With special reference to Cirebon, a region in North-coast Java about 250 km East of Jakana, This article will discuss this issue at some length. The socio-religious function of these celebrations is also explored.DOI: 10.15408/sdi.v6i3.724